KAJIAN KONSENTRASI DAN RASIO GELATIN DARI KULIT IKAN PATIN DAN KAPPA KARAGENAN PADA PEMBUATAN JELI - Eveline .; Joko Santoso; Ivan Widjaja (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2011)
Jelly is a dessert that requires gelling agent on the making process. Besides kappa carrageenan originated from Eucheuma cottonii, the gelatin obtained from catfish skin was also used as the alternative source of gelling agent The purpose of this research was to obtain the best concentration and ratio of patin fish gelatin and kappa carrageenan in jelly formulation, and to study the physical and sensory characteristics of the modified jelly.. The formulation of jellies were combination of concentration and gelling agent ratio (gelatin:kappa carrageenan), which are 1%, 1:1; 1%, 2:1; 1%, 1:2; 2%, 1:1; 2%, 2:1; 2%, 1:2; 3%, 1:1; 3%, 2:1; and 3%, 1:2 respectively. The best combination was determined based on the best score obtained from each test parameters on physical and sensory analyses. The result showed that concentration and gelling agent ratio affect physical and sensory characterstics of the jelly. Jelly with 2% gelling agent and gelatin : kappa carrageenan ratio of 2:1 was the best formula which possessed the closest physical characteristic to the commercial jelly (not significantly different) on gel strength parameter (123.29 g cm) and viscosity (79.90 cPs); although gelling point (32.83 °C), melting point (45.83 °C), pH (5.20), and syneresis degree (0.07%) were significantly different. The best jelly had better syneresis degree compared to the commercial one (lower numeric score). For the sensory characteristic, the best jelly was still less in (chewiness), color (clarity), and overall acceptance.Key words: Eucheuma cottonii, gelatin, jelly, kappa carragenan, patin fish